Modelling of similarity characteristics of polycyclic aromatic hydrocarbons (PAHs) in Sungai Perak, Malaysia via rough set theory and principal component analysis (PCA) - Mustafa S.F.Z.; Mat Deris M.; Abd Manan T.S.B.; Beddu S.; Mohd Kamal N.L.; Mohamad D.; Yavari S.; Qazi S.; Hanafiah Z.; Omar Abu Nassar S.; Yeoh K.L.; Sheriff I.; et al. (Elsevier B.V., 2024)
This paper presents application of rough set theory and PCA for modelling of similarity characteristics of PAHs from Perak River: Tanjung Belanja Bridge (TBB, l1), Water Treatment Plant Parit (WTPP, l2), Parit Town Discharge (PTD, l3), Water Treatment Plant Senin (WTPS, l4), and Water Treatment Plant Kepayang (WTPK, l5). The clustering involved PAHs as attributes and sampling stations as objects. The l1 and l3 were clustered in Simdegx,y?0.8. The Simdegx,y?0.7 was observed in all attributes (except l5) forming two sets of clusters. PCA showed that low molecular weight (LMW) PAHs were prominent with variances of 68.47% (naphthalene, Nap) and 27.63% (carbazole). 2023 Elsevier B.V.